THE EFFECT OF FIRM SIZE, FIRM GROWTH, PROFITABILITY AND CAPITAL STRUCTURE ON FIRM VALUE WITH DEVIDENT POLICY AS INTERVENING VARIABLES IN TELECOMMUNICATION COMPANIES LISTED ON INDONESIA STOCK EXCHANGE - Sutanto, Hermawan (Asosiasi Dosen Akuntansi Indonesia, 2019)
The purpose of this study was to examine the effect of firm size, firm growth, profitability and capital structure on firm value with dividend policy as an intervening variable. The population in this study are telecommunications companies listed on the Indonesia stock exchange (IDX) for the period of 2010-2018. The method of selecting samples uses saturated or census samples. The samples used were 4 companies. The method used in this research is panel data regression method with a significance level of 5% using the common effect model (CEM). Hypothesis testing using t test, f test, and residual test. The results showed that simultaneous firm size, profitability, capital structure has a negative effect on firm value. Partially the variable firm growth, capital structure, and dividend policy have a positive and significant effect on firm value. Firm size, profitability has a positive effect on dividend policy, while partially firm growth, capital structure has a negative effect on dividend policy. Mediation Test results show that the dividend policy is not able to mediate the relationship between firm size, company growth, profitability and capital structure on firm value.